The effects of preconception interventions on improving reproductive health and pregnancy outcomes in primary care: A systematic review - Hussein, N.; Qureshi, N.; Kai, J. (2017)
Background Reproductive health and pregnancy outcomes may be improved if reproductive risk assessment is moved from antenatal to preconception period. Primary care has been highlighted as an ideal setting to offer preconception assessment, yet the effectiveness in this setting is still unclear.